Mechanical Aptitude and Spatial Relations Tests - Barron's Educational Series, inc. (Hauppauge, NY : Barron's, 2009)
This manual presents 18 practice tests in both mechanical aptitude & spatial ability with answers & detailed explanations for all questions.
Keywords: Mechanical ability -- Examinations, questions, etc; Space perception -- Examinations, questions, etc; Reasoning (Psychology) -- Examinations, questions, etc